Crossover scaling in the two-dimensional three-state Potts model - Nagai, T.; Okamoto, Y.; Janke, W. (Condensed Matter Physics, 2013)
We apply simulated tempering and magnetizing (STM) Monte Carlo simulations to the two-dimensional three-state Potts model in an external magnetic field in order to investigate the crossover scaling behaviour in the temperature-field plane at the Potts critical point and towards the Ising universality class for negative magnetic fields. Our data set has been generated by STM simulations of several square lattices with sizes up to 160x160 spins, supplemented by conventional canonical simulations of larger lattices at selected simulation points. We present careful scaling and finite-size scaling analyses of the crossover behaviour with respect to temperature, magnetic field and lattice size. Ми застосовуємо Монте Карло симуляцiї з симульованим темперуванням i намагнiченням (STM) до двовимiрної тристанової моделi Поттса у зовнiшньому магнiтному полi для того, щоб дослiдити кросоверну скейлiнгову поведiнку у площинi температура-поле при критичнiй точцi Поттса, а також клас унiверсальностi моделi Iзинга для негативних магнiтних полiв. Набiр наших даних був згенерований STM симуляцiями декiлькох квадратних ґраток розмiром до 160×160 спiнiв, доповненими звичайними канонiчними симуляцiями бiльших ґраток при вибраних симуляцiйних точках. Ми представляємо ретельний аналiз скейлiнгу i скiнченомiрного скейлiнгу кросоверної поведiнки по вiдношенню до температури, магнiтного поля i розмiру ґратки.